Alkaline Amino Acids for Salt Reduction in Surimi: A Review - Tong Shi; Guxia Wang; Yu Xie; Wengang Jin; Xin Wang; Mengzhe Li; Yuanxiu Liu; Li Yuan (Foods, 2025)
Surimi products are popular due to their high protein and low fat content. However, traditional processing methods rely on high concentrations of salt (2–3%) to maintain texture and stability, contributing to excessive sodium intake. As global health trends advance, developing green and low-salt technologies while maintaining product quality has become a research focus. Alkaline amino acids regulate protein conformation and intermolecular interactions through charge shielding, hydrogen bond topology, metal chelation, and hydration to compensate for the defects of solubility, gelation, and emulsification stability in the low-salt system. This article systematically reviews the mechanisms and applications of alkaline amino acids in reducing salt and maintaining quality in surimi. Research indicates that alkaline amino acids regulate the conformational changes of myofibrillar proteins through electrostatic shielding, hydrogen bond topology construction, and metal chelation, significantly improving gel strength, water retention, and emulsion stability in low-salt systems, with the results comparable to those in high-salt systems. Future research should optimize addition strategies using computational simulations technologies and establish a quality and safety evaluation system to promote industrial application. This review provides a theoretical basis for the green processing and functional enhancement of surimi products, which could have significant academic and industrial value.